Microencapsulated duck oil diacylglycerol: Preparation and application as anti-obesity agent. (March 2019) - Wang, Baowei; Zhang, Mingai; Ge, Wenhua; He, Kelin; Cheng, Fansheng
Abstract: Although duck oil diacylglycerol (DAG) is considered a beneficial food additive, its production, stability and functions are not sufficiently analyzed. In the present study, the alkaline hydrolysis - lipase esterification method was utilized to obtain high purity 1, 3-DAG, and the production rate surpassed 94%. In addition, DAG microencapsulation using sodium caseinate and beta-cyclodextrin was optimized and characterized. The microencapsulated duck DAG (mdDAG) was smooth in surface and cubic in shape, with particle size narrowly distributed between 10 μm and 100 μm with high dispersion. The peroxide values and mass loss values illustrated the evidently inhibitory effects of mdDAG on the oxidation process. Moreover, the effects of mdDAG intake on hyperlipidemic Wistar rats were evaluated systematically via anthropometrical and serum biochemical parameters, organ indexes and histological analysis of the liver. Results indicated that mdDAG intake was safe and acted as a functional ingredient to reduce the body weight, stimulate the lipid metabolism in viscera, and lessen obesity. Highlights: 1, 3- diacylglycerols (DAG) was enzymatically synthesized using duck oil. Duck 1, 3-DAG was microencapsulated to restrain the oxidation process. mdDAG was proved safe and efficient as an anti-obesity agent.